2021
DOI: 10.2196/21088
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Smartphone Apps for Improving Nutritional Status of Pancreatic Cancer Patients: Randomized Controlled Trial

Abstract: Background Approximately 80% of pancreatic ductal adenocarcinoma (PDAC) patients suffer from anorexia, weight loss, and asthenia. Most PDAC patients receive chemotherapy, which often worsens their nutritional status owing to the adverse effects of chemotherapy. Malnutrition of PDAC patients is known to be associated with poor prognosis; therefore, nutritional management during chemotherapy is a key factor influencing the outcome of the treatment. Mobile apps have the potential to provide readily ac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 61 publications
1
15
0
Order By: Relevance
“…These studies can be found in Table 2 . Each app had different features, including digital diaries [ 7 , 44 - 49 ], coach feedback [ 7 , 44 - 47 , 49 - 51 ], personalized physical exercise programs and nutrition plans [ 49 , 50 ], general nutrition and physical exercise guidelines [ 45 , 51 ], psychological support courses [ 45 , 51 ], a secure message portal to their health care teams [ 7 , 48 ], health knowledge education [ 46 , 48 , 51 ], and daily tasks [ 48 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…These studies can be found in Table 2 . Each app had different features, including digital diaries [ 7 , 44 - 49 ], coach feedback [ 7 , 44 - 47 , 49 - 51 ], personalized physical exercise programs and nutrition plans [ 49 , 50 ], general nutrition and physical exercise guidelines [ 45 , 51 ], psychological support courses [ 45 , 51 ], a secure message portal to their health care teams [ 7 , 48 ], health knowledge education [ 46 , 48 , 51 ], and daily tasks [ 48 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, information about the disease and treatment, some apps also contain nutritional information or weight management information. The ‘Noom’ app for example is a weight management app commercially available on Google Playstore and Apple Appstore, that was adapted for pancreas cancer patients undergoing chemotherapy [36] and esophageal cancer patients with neoadjuvant chemotherapy [25 ▪▪ ]. The app version for pancreas cancer patients includes daily articles about health knowledge and how to organize the diet and caloric intake especially for pancreas cancer patients.…”
Section: Resultsmentioning
confidence: 99%
“…Only apps for adolescence and adult cancer patients were included. In total, we included 19 studies out of 564 for this narrative review [20,21 ▪ ,22–24,25 ▪▪ ,26,27 ▪▪ ,28 ▪ ,29 ▪ ,30–32,33 ▪ ,34 ▪▪ ,35,36,37 ▪▪ ,38].…”
Section: Methods Search Strategymentioning
confidence: 99%
“… 37 , 39 , 111 , 112 and have been used in assessing treatment effects and benefits. 113 As such, DHTs hold promise in patient-centered drug development, particularly in studying the impact of treatments on physical function, a primary focus in drug trials and multimodal interventional trials for cachexia.…”
Section: Path Forward With Digital Measures Of Real-world Physical Be...mentioning
confidence: 99%